The Meaning Of Native Papuanese Women Towards Violence Against Women In Radar Sorong Newspaper - Ikhsanti Syafaati; Dr. Hapsari Dwiningtyas, S.Sos, MA (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
Papua is a province with the highest number of cases of violence against women. Vulnerability Papuan women subjected to violence due to various factors such as high domestic violence, patriarchal cultural values and customs system, economic problems, and liquor. Newspapers Radar Sorongmerupakan one of the mass media that contains various news about cases of violence against women in Papua. This study aimed to describe the diversity of meanings indigenous Papuan women against violence news in newspapers Radar Sorong. Syntagmatic and paradigmatic analysis of Ferdinand Sussaure used to determine the meaning offered by the media. This study used a qualitative approach-descriptive analysis method Stuart Hall reception. Data collected by indepth interview to ten informants who read the paper sliding radar. These results indicate the dominant meaning in the news in the newspaper Radar Sorong violence that abused women are still portrayed as passive, weak, and helpless. From the comparison between the preferred reading with the informant interviews there are four informants who are in the dominant position in the research reading through meaning informants tend to be similar to those shown by sliding radar. And six informants in a position Negotiaded Reading which has its own arguments concerning the meaning of the displayed radar sliding and no informants who are in a position oppositional reading.